Level Of Motor Educability In Floor Gymnastics Courses To Motion Skills - Hilmy Aliriad (JUARA : Jurnal Olahraga, 2023)
This study aimed to determine the influence of the level of motor education on movement skills in floor gymnastics courses. The story of motor education is significant because it will affect a person's ability to learn better motion skills. The research method used in this study is a quantitative research design with an experimental approach. The research instrument used in this study is a test of motor educability and observation of motion skills with a sample of 30 students selected by random sampling. Correlation data were processed using SPSS Version 21. The results showed that the level of motor educability positively affects movement skills in floor exercise courses because a high level of motor educability will improve movement skills in floor exercise courses and improve the ability to coordinate movements. Overall, students have a good level of motor educability and motor skills. Further studies are needed to determine factors beyond motor educability and Motion Skills.